Factors affecting mortality and disbursement of insurance benefits to female members of BRAC village organization - Chowdhury, A Mushtaque R; M Showkat Gani (BRAC Research and Evaluation Division (RED), 2019)
BRAC has been implementing multi faceted programmes such as rural development programme, education prograrnme, health and nutrition programme for poverty alleviation. The core of rural development programme IS the fom1ation of village organizations (VO) . Through the YOs BRAC organizes the poor (BRAC members), and provide them with credit facility and other technical support. Unlike developed countries, taking up life insurance policy is not very common in Bangladesh. In 1990, BRAC introduced a life insurance scheme for its YO members. At the death of any member BRAC pays Tk. 5000 for each claim from the interest fund of the micro finance programme. There are some eligibility of receiving the insurance claims; however, all members are entitled to the insurance. In 1998, 3,879 VO members died and the insurance claims of a total of Tk. 19,395,000 was paid to their nominees. The mam goals of this study were to find out the causes of death and mortality differentials of BR;\C members and also to look at the settlement of insurance claims of BRAC members. To know the hum:m health status, mortality is the key indicator. It is hardly found the mortality study among BRAC members (adult female) . So Research and Evaluation Di\'ision (RED) took an initiative to study the BRAC members who died in 1998. Before actual study a pilot survey was carried out in Tangail and Sylhet regionsa during December 1999 - February :woo and survey methods and tools were tested and finalised . Based on the learning from the pilot survey, RED therefore decided to conduct a crosssectional sample survey. The broad objective of this study was to assess the death rates of BRAC YO members in 1998 and also to provide the sociodemographic determinants of mortality and causes of "Region constitutes of 12-20 BR..AC areas which consists of 160 units each with 50 target households to form a village organization.